Thyristor Based Marx Impulse Generator Circuit Prototype for Pulsed Inductive Thruster (PIT) Propulsion System - Karlo, Aditya Adriano; Yohandri, Y; Asrizal, A; Mairizwan, M (PILLAR OF PHYSICS, 2025)
Pulsed Inductive Thruster is a type of electric propulsion system for spacecraft. It requires high voltages to operate, wherein a Marx impulse generator circuit is used. This circuit requires a switching component, which in the most basic form of such circuit is a spark gap switch. A spark gap switch undergoes rapid degradation whilst in use, which limits its lifespan before needing replacement; a hindrance for operations in space. To circumvent this problem, solid state switches might be used in the stead of spark gap switches. One such switch is a thyristor, whose feasibility was tested in this research. A four-stage basic form of the Marx impulse generator circuit had its spark gap switches replaced with thyristors, and a control unit fitted. Inputs at 2, 4, 6, and 8 volts were given, resulting in outputs at average 0.5, 1.4, 2.1, and 3.1 volts, with σ 0.095, 0.14, 0.1, and 0.1 respectively. These results do not indicate that thyristors might be feasible as an alternative to spark gap switches.